2015
DOI: 10.1038/ncomms10224
|View full text |Cite|
|
Sign up to set email alerts
|

RSV-specific airway resident memory CD8+ T cells and differential disease severity after experimental human infection

Abstract: In animal models, resident memory CD8+ T (Trm) cells assist in respiratory virus elimination but their importance in man has not been determined. Here, using experimental human respiratory syncytial virus (RSV) infection, we investigate systemic and local virus-specific CD8+ T-cell responses in adult volunteers. Having defined the immunodominance hierarchy, we analyse phenotype and function longitudinally in blood and by serial bronchoscopy. Despite rapid clinical recovery, we note surprisingly extensive lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
311
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(344 citation statements)
references
References 44 publications
13
311
1
2
Order By: Relevance
“…Recently, these have been permitted on ethical review with assurances that they are carried out in clinical units with track records of safety and evidence of sufficient staffing and training. These have allowed direct access to respiratory mucosa, enabling sampling of local immune cells and epithelia, which is understood to be critical for further understanding of how to limit respiratory viral disease in man [17].…”
Section: Logistical and Ethical Issues In Deliberately Infecting Withmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, these have been permitted on ethical review with assurances that they are carried out in clinical units with track records of safety and evidence of sufficient staffing and training. These have allowed direct access to respiratory mucosa, enabling sampling of local immune cells and epithelia, which is understood to be critical for further understanding of how to limit respiratory viral disease in man [17].…”
Section: Logistical and Ethical Issues In Deliberately Infecting Withmentioning
confidence: 99%
“…We recently investigated the role of virus-specific T cells in RSV infection in the experimental human infection model [17]. Using MHC-peptide tetramers, we labelled and tracked RSV-specific CD8+ T cells in blood and airways of experimentally infected volunteers, sampling the lower airway by bronchoscopy.…”
Section: Experimental Challenge Provides Insights Into Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Although antibody induction is the major goal of vaccination against RSV disease, the recent demonstration that local mucosal CD8 T cells play a part in controlling viral load offers the prospect that T cell induction by vaccines might also be beneficial [87][88][89] .…”
Section: Antigenic Targets For Prophylaxis and Vaccinationmentioning
confidence: 99%
“…Nonetheless, the deleterious impact of RSV infection on pediatric health is still difficult to avoid because no RSV vaccine has yet been authorized for clinical use (3). The development of RSV vaccine has been hampered by concerns about its safety and effectiveness, given that the first RSV vaccine clinical test in the 1960s showed that children previously inoculated with formalin-inactivated RSV vaccine (FIRSV) consequently suffered with enhanced respiratory disease after subsequent RSV exposure (4,5).…”
Section: Introductionmentioning
confidence: 99%